Self-evaluated burden in adults with attention-deficit hyperactivity disorder (ADHD): a pilot study - Mattos,Paulo (2010)
OBJECTIVES: To investigate feasibility and easiness of administration of a brief and simple instrument addressing impairment associated with adult attention deficit hyperactivity disorder (ADHD) and if ADHD subtypes were correlated to specific profiles of self-reported impairment. METHODS: Thirty-five adults (19 men and 16 women; mean age of 31.74 years) diagnosed with ADHD according to DSM-IV with a semi-structured interview (K-SADS PL) were asked to fill out a Likert scale covering six different functional areas (academic, professional, marital, familiar, social and daily activities). Clinicians questioned patients about their understanding of the questionnaire and investigated their answers in more details to check consistency of their answers. RESULTS: No patient reported difficulties in understanding the questionnaire. Further questioning of patients' answers confirmed their choices in the six areas. Academic burden had the highest average score in the whole sample, followed by professional burden. Social area had the lowest average score in this sample.